Agroecologia e transformações no espaço rural: o caso do assentamento Conquista da Liberdade, Piratini, RS - Kunzler, Edinho Carlos (2009)
This work deals with the agrarian issue in Brazil bringing as a main point a collective organization of an agrarian reform settlement, which consists in a project that seems to be viable to constitute a social and agricultural distinct model if compared to the individualistic one. Such a project also provides the main objective of the group, that is, to stay on the piece of earth where they settle down. In order to understand the way the settlement group Conquista da Liberdade , located in Piratini, Rio Grande do Sul, is organized and also the way it leads its space-time regarding Geography theories, based specially on Milton Moraes works and his qualitative analyses methodologies, a materialistic-historical approach of its constitution and evolution process was done. The most important contribution brought up to the discussion in this work is the one about the subject constitution from their limitations undergone through their lives. The obstacles imposed to the personal success were overcome through collective consciousness raising, process initiated before entering the settlement. The settlement also contributed to the political formation of the group and opened doors to a new social model based not only on cooperation but also on a collective project of organization. The family settlements did not mean the initial problem solution, that is, the piece of earth loss, but it also brought up divergences that were empowered by the initial difficulties and it led to the break of the big collective group of 50 families. The current group that is formed by 17 families that are part of the COOPAVA Cooperativa Agrícola Vista Alegre Limitada (Agriculture Cooperative Vista Alegre Limited) constructed a new way to reach its expectations, that is, they adopted the agro-ecological praxis on their daily activities, which broke up with the conventional model agricultural activities. Moreover, it took seriously the responsibility and conduction strategy not only for their activities but one that is concerned with planning for the future generations.